Lack of Arginine Vasopressin–Induced Phosphorylation of Aquaporin-2 Mutant AQP2-R254L Explains Dominant Nephrogenic Diabetes Insipidus - Fabrizio De Mattia; Paul J.M. Savelkoul; Erik‐Jan Kamsteeg; Irene B. M. Konings; Peter van der Sluijs; R. Mallmann; A. Oksche; Peter M.T. Deen (2005)
Water homeostasis in humans is regulated by vasopressin, which induces the translocation of homotetrameric aquaporin-2 (AQP2) water channels from intracellular vesicles to the apical membrane of renal principal cells. For this process, phosphorylation of AQP2 at S256 by cAMP-dependent protein kinase A is thought to be essential. Mutations in the AQP2 gene cause recessive and dominant nephrogenic diabetes insipidus (NDI), a disease in which the kidney is unable to concentrate urine in response to vasopressin. Here, a family in which dominant NDI was caused by an exchange of arginine 254 by leucine in the intracellular C terminus of AQP2 (AQP2-R254L), which destroys the protein kinase A consensus site, was identified. Expressed in oocytes, AQP2-R254L appeared to be a functional water channel but was impaired in its transport to the cell surface to the same degree as AQP2-S256A, which mimics nonphosphorylated AQP2. In polarized renal cells, AQP2-R254L was retained intracellularly and was distributed similarly as AQP2-S256A or wild-type AQP2 in unstimulated cells. Upon co-expression in MDCK cells, AQP2-R254L interacted with and retained wild-type AQP2 in intracellular vesicles. Furthermore, AQP2-R254L had a low basal phosphorylation level, which was not increased with forskolin, and mimicking constitutive phosphorylation in AQP2-R254L with the S256D mutation shifted its expression to the basolateral and apical membrane. These data indicate that dominant NDI in this family is due to a R254L mutation, resulting in the loss of arginine vasopressin–mediated phosphorylation of AQP2 at S256, and illustrates the in vivo importance of phosphorylation of AQP2 at S256 for the first time.